2017
DOI: 10.1097/npt.0000000000000200
|View full text |Cite
|
Sign up to set email alerts
|

Motor Imagery Training After Stroke: A Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Our review reported a high heterogeneity in methodological quality of the studies and conflicting results. More high-quality studies and greater standardization of interventions are needed to determine the value of MI for persons with stroke.Video Abstract available for more insights from the authors (see Video, Supplemental Digital Content 1, http://links.lww.com/JNPT/A188).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
1
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 45 publications
3
72
1
4
Order By: Relevance
“…Improving walking ability among people after a stroke is considered as a critical goal of rehabilitation (Braun et al, 2006;Dunsky et al, 2006;Dunsky et al, 2008). The possibility of a MI practice to supplement the rehabilitation process was proven in several studies (Braun et al, 2006;de Vries et al, 2013;Dickstein et al, 2004;Dickstein & Deutsch, 2007;Dunsky et al, 2006;Dunsky et al, 2008;Guerra et al, 2017;Kho et al, 2014;Kumar et al, 2016;Lee et al, 2011;Li et al, 2017;Malouin & Richards, 2010;Mulder, 2007;Stevens & Stoykov, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving walking ability among people after a stroke is considered as a critical goal of rehabilitation (Braun et al, 2006;Dunsky et al, 2006;Dunsky et al, 2008). The possibility of a MI practice to supplement the rehabilitation process was proven in several studies (Braun et al, 2006;de Vries et al, 2013;Dickstein et al, 2004;Dickstein & Deutsch, 2007;Dunsky et al, 2006;Dunsky et al, 2008;Guerra et al, 2017;Kho et al, 2014;Kumar et al, 2016;Lee et al, 2011;Li et al, 2017;Malouin & Richards, 2010;Mulder, 2007;Stevens & Stoykov, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Based on its potential for relearning skills, MI has become a target for many researchers in the field of neurology and especially in stroke rehabilitation, at all stages (Braun, Beurskens, Borm, Schack, & Wade, 2006;Dickstein & Deutsch, 2007;Guerra, Lucchetti, & Lucchetti, 2017;Jackson et al, 2001;Kho, Liu, & Chung, 2014;Malouin, Jackson, & Richards, 2013). Using MI interventions in treatment has been manipulated to engage motivation, cognitive processes, motor control and sensory feedback-based learning mechanisms (Li, Li, Tan, Chen, & Lin, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On these bases, motor imagery has been successfully applied as motor learning technique (Avanzino et al, 2015;Di Rienzo et al, 2016;Ruffino et al, 2017;Bisio and Bove, 2018;. Moreover, it has been suggested as promising add-on to physical therapy in facilitating motor recovery in neurological patients (Abbruzzese et al, 2016;Guerra et al, 2017;Hanson and Concialdi, 2019) and to the conventional training in different sport domains for improving motor performance (Guillot and Collet, 2008;Bisio and Bove, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Motor imagery (MI) is a key technique in motor learning and motor control facilitating brain plasticity (Shumway-Cook and Woollacott, 2007 ). MI, which is an established training technique from sports sciences, was recently introduced to the field of neurorehabilitation, in particular to stroke rehabilitation (Braun et al, 2013 ; Guerra et al, 2017 ). Decety and Grezes defined MI as “…a dynamic state during which the representation of a given motor act is internally rehearsed without any motor output.” (Decety and Grezes, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, McInnes et al found that patients with a brain lesion in the parietal and frontal lobes might not benefit from MI training. However, just recently, Guerra et al summarised the beneficial effect of MI on activities of daily living, balance, lower limbs and gait, as well as upper limb function without limitation to specific brain lesions (Guerra et al, 2017 ). For patients with PD, Caligiore et al postulated that the effect of MI in PD could be influenced by the duration of the disease.…”
Section: Introductionmentioning
confidence: 99%